BMAL1-Downregulation Aggravates Porphyromonas Gingivalis-Induced Atherosclerosis by Encouraging Oxidative Stress. Issue 6 (13th March 2020) - Xie, Mengru; Tang, Qingming; Nie, Jiaming; Zhang, Chao; Zhou, Xin; Yu, Shaoling; Sun, Jiwei; Cheng, Xiang; Dong, Nianguo; Hu, Yu; Chen, Lili
Abstract : Rationale: Atherosclerotic cardiovascular diseases are the leading cause of mortality worldwide. Atherosclerotic cardiovascular diseases are considered as chronic inflammation processes. In addition to risk factors associated with the cardiovascular system itself, pathogenic bacteria such as the periodontitis-associated Porphyromonas gingivalis ( P gingivalis ) are also closely correlated with the development of atherosclerosis, but the underlying mechanisms are still elusive. Objective: To elucidate the mechanisms of P gingivalis -accelerated atherosclerosis and explore novel therapeutic strategies of atherosclerotic cardiovascular diseases. Methods and Results: Bmal1 −/− (brain and muscle Arnt-like protein 1) mice, ApoE −/− mice, Bmal1 −/− ApoE −/− mice, conditional endothelial cell Bmal1 knockout mice ( Bmal1 fl/fl ; Tek -Cre mice), and the corresponding jet-legged mouse model were used. P gingivalis accelerates atherosclerosis progression by triggering arterial oxidative stress and inflammatory responses in ApoE −/− mice, accompanied by the perturbed circadian clock. Circadian clock disruption boosts P gingivalis -induced atherosclerosis progression. The mechanistic dissection shows that P gingivalis infection activates the TLRs-NF-κB signaling axis, which subsequently recruits DNMT-1 to methylate the BMAL1 promoter and thus suppresses BMAL1 transcription. The downregulation of BMAL1 releases CLOCK, which phosphorylates p65 and further enhances NF-κB signaling, elevating oxidative stress and inflammatory response in human aortic endothelial cells. Besides, the mouse model exhibits that joint administration of metronidazole and melatonin serves as an effective strategy for treating atherosclerotic cardiovascular diseases. Conclusions: P gingivalis accelerates atherosclerosis via the NF-κB-BMAL1-NF-κB signaling loop. Melatonin and metronidazole are promising auxiliary medications toward atherosclerotic cardiovascular diseases. Abstract : Supplemental Digital Content is available in the text.